Genetic Control of the Secondary Modification of Deoxyribonucleic Acid in Escherichia coli - Mamelak, Linda (1970)
The wild-type restriction and modification alleles of Escherichia coli K-12 and B were found to have no measurable effect on the patterns of methylated bases in the deoxyribonucleic acid (DNA) of these strains. The genetic region controlling the methylation of cytosine in E. coli K-12 was mapped close to his, and the presence or absence of this gene in E. coli B or E. coli K had no effect on the restriction and modification properties of these strains. Thus, only a few of the methylated bases in the DNA of these strains are involved in host modification, and the biological role of the remainder remains obscure.